Expression of haemagglutinin-neuraminidase of newcastle virus genotype VIII in insect cell Sf9 - Le, Van Truong; Man, Hong Phuoc; Dong, Van Quyen (Academia Journal of Biology, 2024)
The hemagglutinin-neuraminidase (HN) protein is the surface glycoprotein of Newcastle disease virus (NDV) which is involved in the process of virus entry into host cells. HN exhibits the capability to induce agglutination of chicken red blood cells, thereby contributing to the viral infection of the host. As a consequence, HN is a potential antigen for the production of subunit vaccines for protecting poultry from NDV infections. In this study, the hn gene coding for the HN antigen of NDV genotype VIII was artificially synthesized, ligated into donor vector pFastBacHT A and integrated into the baculovirus genome for the purpose of HN expression in Spodoptera frugiperda 9 (Sf9) cells. The recombinant HN protein was successfully expressed in Sf9 cells in the SF900 III medium. The expressed recombinant HN protein, with a size of approximately 63 kDa, exhibited hemagglutinin activity (HA) of 4log2 when interacting with chicken erythrocyte fluid. The findings of this study lay the foundation for subsequent research endeavors aimed at the development of Newcastle disease virus (NDV) vaccines tailored for poultry in Vietnam.